Craniomandibular Variation in Phalangeriform Marsupials: Functional Comparisons with Primates. Issue 2 (13th January 2018) - ST Clair, Elizabeth M.; Reback, Nicholas; Perry, Jonathan M. G.
ABSTRACT: Phalangeriform marsupials have often been compared with primates because of similarity in the range of external morphology, ecological niches, and body size between the two radiations. We explore morphological convergence in the masticatory anatomy of strepsirrhine primates and phalangeriforms, through osteological measurements of the mandible and facial skeleton, and through dissection of the masticatory musculature, presenting new data on the arrangement and proportions of jaw adductors in phalangeriforms. Phalangeriforms and primates have a large number of shape differences in mandibular morphology. Despite these differences in shape on phylogenetic lines, dietary groups used to pool species of phalangeriforms and strepsirrhines also differed from each other in a range of shape variables. Notably, the striped possum ( Dactylopsila ), previously described as convergent with the aye‐aye ( Daubentonia ), shares a number of features of mandibular shape with Daubentonia, and the exudate‐feeding sugar‐glider, Petaurus, shares shape features with gummivorous strepsirrhines. Petaurus also has long‐fibered jaw adductors for its body mass, as would be expected for a species with a requirement for large gape. Phalangeriform species on the frugivore‐folivore continuum were less clearly comparable to strepsirrhine species with similar diets. There are a number of significant dietary contrasts in osteological measurements, but in the masticatory muscles phalangeriforms did not meet all expectations based on available dietary data, highlighting the possible complexity of dietary adaptation in phalangeriform folivores. Anat Rec, 301:227–255, 2018. © 2018 Wiley Periodicals, Inc.